2020
DOI: 10.1002/smll.202001883
|View full text |Cite
|
Sign up to set email alerts
|

Role of Artificial Intelligence and Machine Learning in Nanosafety

Abstract: Robotics and automation provide potentially paradigm shifting improvements in the way materials are synthesized and characterized, generating large, complex data sets that are ideal for modeling and analysis by modern machine learning (ML) methods. Nanomaterials have not yet fully captured the benefits of automation, so lag behind in the application of ML methods of data analysis. Here, some key developments in, and roadblocks to the application of ML methods are reviewed to model and predict potentially adver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
83
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 99 publications
(88 citation statements)
references
References 102 publications
(66 reference statements)
0
83
0
Order By: Relevance
“…In the past decade, a variety of data driven computational approaches, such as Quantitative Structure-Activity Relationship (QSAR) models and read-across approaches that use diverse machine learning methods, have been used to predict NM-related toxicity [ 10 , 148 ]. The goal of these methods is to map the material description and intrinsic/extrinsic physicochemical properties to the biological outcomes to identify NM properties of concern, and facilitate design of NM that avoid, reduce or modulate these properties [ 150 , 151 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the past decade, a variety of data driven computational approaches, such as Quantitative Structure-Activity Relationship (QSAR) models and read-across approaches that use diverse machine learning methods, have been used to predict NM-related toxicity [ 10 , 148 ]. The goal of these methods is to map the material description and intrinsic/extrinsic physicochemical properties to the biological outcomes to identify NM properties of concern, and facilitate design of NM that avoid, reduce or modulate these properties [ 150 , 151 ].…”
Section: Resultsmentioning
confidence: 99%
“…This is particularly important for virtual NM not yet synthesized, where prediction of their properties is important. An overview of various computational models for NMs is given in recent reviews [ 10 , 150 , 151 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 7 ] Although numerous studies have been conducted for nanosafety evaluation using in silico, in vitro, and in vivo methods, a widely accepted assessment framework for ENMs remains to be built. [ 8–10 ]…”
Section: Introductionmentioning
confidence: 99%
“…According to a study by Törnqvist et al (2014), data from 36 relevant projects demonstrated major (i.e., 53%) reductions in the use of animals in pharmaceutical development [ 27 ]. Taking into account the cost and working hours associated with in vivo and in vitro experiments and that traditional “wet-lab” toxicology cannot keep up with diversity and increasing abundance of engineered NPs, computational modelling has the potential to act as a high-throughput alternative [ 28 , 29 ] and is becoming increasingly accepted in regulatory testing as model validation and documentation improves.…”
Section: Introductionmentioning
confidence: 99%